Is standard superior while learning language? - Khamzayeva, Mukaddas (Результаты научных исследований в условиях пандемии (COVID-19), 2022)
Language is considered to be a tool helping people to communicate with each other. It can be developed throughout the years inparallel with society due to diverse factors. In consequence, different variations of the same language may occur. With a range of differentvariation people may have to decide on a model as a standard to use in mass media or to educate at different educational institutions. How do people choose a variation as a standard? Are there any criteria for a language to be considered as a standard? While teaching a language which one is supposed to be taught? This article will provide some answers regarding to these questions